Accuracy of Conventional Triplane Measures Compared to 3-D Analysis for Assessment of Cubitus Varus Deformities in Adults - Yoon GS; Oh WT; Chun YM; Koh IH; Kang HJ; Choi YR (Dove Medical Press, 2020)
Gil-Sung Yoon, Won-Taek Oh, Yong-Min Chun, Il-Hyun Koh, Ho-Jung Kang, Yun-Rak Choi Department of Orthopedic Surgery, Severance Hospital, Yonsei University College of Medicine, Seoul 03722, South KoreaCorrespondence: Yun-Rak ChoiDepartment of Orthopedic Surgery, Yonsei University College of Medicine, 50-1 Yonsei-ro, Seodaemun-gu, Seoul 03722, Republic of KoreaTel +82-2-2228-2183Fax +82-2-363-1139Email YRCHOI@yuhs.acPurpose: Cubitus varus is a common triplane deformity in adults associated with supracondylar humeral fractures experienced as a child and consists of varus, extension, and internal rotation components. When corrective osteotomy is indicated, these three components should be measured precisely. This study aimed to evaluate the accuracy of radiographic and physical measurements of cubitus varus deformities in adults compared to values measured on three-dimensional (3-D) bone surface models of the adult bilateral humerus.Methods: Three-dimensional bilateral humerus models were developed using bilateral humerus CT images of 20 adult patients with cubitus varus. The varus, internal rotation, and extension components of the deformity were assessed by superimposing the 3-D bone model onto a mirror-image model of the contralateral normal humerus. Values obtained from the radiographic and physical measurements were compared with those from the 3D model. The reliability of each measurement was assessed by calculating correlation coefficients (CCs).Results: Radiographic measurements of the varus and extension components showed good reliability (CC = 0.796 and 0.791, respectively). Physical measurement of the varus component, however, showed only moderate reliability (CC= 0.539), while physical measurement of the extension and internal rotation components exhibited poor reliability (CC = 0.164 and 0.466, respectively).Conclusion: Varus and extension components of cubitus varus in adults can be reliably measured using conventional methods, whereas the internal rotation component cannot. Thus, 3-D methods with which to quantify the rotational component preoperatively might be needed when the correction of a rotational deformity is considered.Keywords: cubitus varus, preoperative evaluation, triplane measurement, computed tomography